Вы находитесь на странице: 1из 23

1

1.

1.1.

1.1.1.


(), ,
. ,
A A p 1 p . -
n A k -

Pn (k ) = C nk p k (1 p ) .
nk

, ,

= k (k = 0,1,..., n ) Pn (k ) . -
:

Pn (k ) n = const
p = const
1

0 1 2 3 5 6 k
4

,
, - -
0 1:

0 1 1 0

1 2 3 n

p - n - -
; Pn (k ) - , k .

. -
(), .
2
i - (t ) (t ) :
(i )

(i ) (t )

x1

t
t1

x1 - 1 , -
(t ) t1 .
, -
( -
):

F ( x ) = P{ x},

P{A} A .
F (x ) :

F (x
1

x
0

F (x ) = P{ = x } k
xk x

F (x )

xn 1 xn xn+1 ... x
...
3
( )
:
dF ( x )
W ( x ) = .
dx

W (x ) :

W (x )

:
x2

P{x1 x2 } = W ( x )dx .
x1

W ( x ) = P{ = xk } ( x xk ) .
k

-
, :

W ( x ) = W( ) ( x ) + W( ) ( x ) ,

: W (x )dx = 1 .

: (t )
y = f ( x ) :

x0
x
x0
4
= f ( ) . , x
y ,

x, x x 0

y = f (x ) =
x 0 signx, x > x 0 .

W ( y ) = W( ) ( y ) + W( ) ( y ) .

, ,

W ( y ) y x0
W( ) ( y ) =
0 y > x0 .

Wn ( y ) = P{ = x0 } ( y + x0 ) + P{ = x0 } ( y x0 ) =
= P{ x0 } ( y + x0 ) + P{ > x0 } ( y x0 ) =
= F ( x0 ) ( y + x0 ) + [1 F ( x0 )] ( y x0 ) .



0, y > x0
y

F ( y ) = F ( x0 ) + W ( x )dx, x0 y < x0
x0
x0

F ( x0 ) + 1 F ( x0 ) + W ( x )dx = 1, y x0 .
x0
5

W (x)

F ( x0 ) 1 F ( x 0 )

x0 x0 x
0
f (x )

x0
x0 x
0

W ( y )

1 F ( x0 )
F ( x0 )

y
x0 0 x0

F ( y )
1

y
x0 0 x0

, -
W ( y ) , ,
.

1.1.2.


. k - (-
):

n
mk { } = x W (x )dx;
k
mk { } = P{ = xi }xik .
i =1
6
k - :
n
M k { } = (xi m1{ }) W ( x )dx; M k { } = P{ = xi }(xi m1{ }) .
k k

i =1

, (-
):

n
m1 { } = xW (x )dx; m1{ } = P{ = xi }xi ;
i =1
n
M 2 { } = (xi m1{ }) W (x )dx; M 2 { } = P{ = xi }( xi m1{ }) .
2 2

i =1

m1 { } :

M 2i +1 { } = 0 (i = 0,1,2,...) .
,

M 1{ } = [x m { }] W (x )dx = 0 .

1

M 3 { } - , -
.

M3
1 =
M 23

.
, ,
1
W ( x ) = e( x a )
2
2 2
,
2

M 3 = 0 , , 1 = 0. ,

x
W ( x ) =
2
2 2
ex ,
2

1 0,63
-
W (x ) ( ):

M4
2 = 3.
M 22

, 2 = 0 . -
2 0,23 .
7
1 , 2 ,
.

1.2.

1.2.1.

, , -
.
t1 , t 2 ,...,
, i - -
(t ) :

(i ) (t )

t3

t2
t
t1 t4


1 = (t1 ), 2 = (t 2 ),..., n = (t n ) .
(n )
n - (t ), -
(n )
x = (x1 ,..., xn ).

n (n )
P i xi = F x (n ) ( )
i=1

n -
(n )
, 1 ,..., n .
,

Fi ( xi ) = F (,..., , xi , ,... ) .
(n )


(x ( ) ) = F (x ),
n
(n ) n
F i i
i =1

1 ,..., n .
n -

W
(n )
(x ) =
(n ) n F
(n )
(x ( ) )
n

x1 ,..., xn
8
n - (n ) ,
1 ,..., n .

x1 xn

F
(n )
(x1 ,..., xn ) = ... W (n ) (x1 ,..., xn ) dx1...dxn ,

:


F
(n )
(,.., ) = ... W (n ) (x1 ,..., xn ) dx1...dxn = 1 .

, ,

n
W
(n )
(x1 ,..., xn ) = W (xi ) . i
i =1
:
xi

F
(n )
(,..., , xi , ,..., ) = ... W (n ) (x1 ,..., xn ) dx1 ...dxn dxi .
( x )

i


F(n ) (,..., , xi , ,..., ) = Fi ( xi ) .

,
xi

Fi (xi ) = ... W (x ,..., x )
(n )
1 n dx1 ...dxn dxi .
( xi )

i :

Wi ( xi ) = ... W (x ,..., x )dx ...dx
( ) n
1 n 1 n .
( xi )

1.2.2.

-
:


mk1 ...kn {1 ,..., n } = ... x1k1 ...xnkn W (x1 ,..., xn )dx1...dxn
(n )
;


M k1 ...kn {1 ,..., n } = ... [x1 m1 {1 }] 1 ...[x n m1 { n }] n W(n ) ( x1 ,..., x n )dx1 ...dxn .
k k

i :

mki { i } = ... xikiW (x1 ,..., xn )dx1...dxn = xik W (xi )dxi ;
(n ) i
i

9

ki ki

M ki { i } = ... [xi m1 {xi }] W (x1 ,..., xn )dx1 ...dxn = [xi m1 {xi }] Wi ( xi )dxi .
(n )


:

M 11 { i , j } = ... ( xi m1{ i })(x j m1 { j })W (x , x )dx dx
(2 )
i j i j = K ij

- i j .
K ij :

x x W (x , x )dx dx m1{i } m1 { j } = m11 { i , j } m1{ i } m1 { j }.


( ) 2
K ij = i j i j i j

:
K ij
Rij =
M 2 { i }M 2 { j }
i j .

, i , j :

K ij = x x W (x )W (x )dx dx

i j i i j j i j m1 { i } m1 { j } = m1 { i } m1 { j } m1 { i } m1 { j } = 0.

, K ij = 0 , . ,
.
.
.
i , j i , j :
i m1 { i } j m1 { j }
i = ; j = ,
M 2 { i } M 2 { j }

xi , x j .

(x )

L= i x j W
2 (2 )
(x , x )dx dx
i j i j =

2

(x ) W (x )dx + (x )


W j (x j )dx j 2 xi x j W (xi , x j )dxi dx j = 2(1 Rij ) 0.
2 2 (2 )
= i i i j

i

, , , :
10

Rij 1 .

, Rij = 1. , L
, L = 0 . ,
i , j xi = x j , .. i = j ,

M 2 { i } M 2 {i } M 2 { i }
i =
M 2 { j }
( j m1{ j }) + m1{i } = M 2 { j }
j + m1{i }
M 2 { j }
m1 { j } ,

i = a j + b .
, Rij = 1 , L -
, i = j , i = a j + c .

, Rij = 1 i j .

1 1 ( x1 a1 )2 ( x1 a1 )( x2 a2 ) (x2 a2 )
2
W
(2 )
(x1 , x2 ) = exp 2r + ,
2(1 r ) 1
2
2 1 r 2 1 2
2
1 2 22


a1 = m1 {1 }; a 2 = m1 { 2 };

12 = M 2 {1 }; 22 = M 2 { 2 } .
:
r 1 2
K12 = r 1 2 , .. R12 = =r.
12 22

(r = 0 ) :

1 1 ( x1 a1 )2 1 ( x2 a2 )2
W
(2 )
(x1 , x2 ) = exp = W1 (x1 ) W2 ( x2 ).
2 1 2 2 1
2
2 2
2

: -
.

1.3.

1.3.1. .

, n -
k ,
11

Pn (k ) = C nk p k (1 p )
nk
.

C p k (1 p )
nk
: k
n = 1.
k =0

: m1 { } = np; M 2 { } = np(1 p ) .

x
( p) ( -
1 p ), ,
. , ,
, +1 -1 .

Pn(m ) , P0(0 ) = 1 - ( )
n m :

x
-2 -1 0 1 2 . . . . . . . . . m. .. l

x = m
l l = l m ,
l + l = n .

:
l + l m = n ,

m+n
l = .
2

Pn(m ) , n -
m+n
. -
2
( ). ,

n+ m n+m
m+n nm
Pn(m ) = Pn = Cn 2 p 2
(1 p ) 2 .
2

n m n, .. 0k n.

n Pn (k ) .
Pn (k ) n p = 0,5 :
12

Pn (k ) Pn (k )

0,5 n =1 (m = 2k 1) 0,5
n=2 (m = 2k 2)

0,25

k k
0 1 2 0 1 2

Pn (k ) Pn (k )

0,5 0,5
0,4
n=3 (m = 2k 3) 0,4
n=4 (m = 2k 4)
0,3 0,3
0,2 0,2
0,1 0,1
k k
0 1 2 3 4 0 1 2 3 4

Pn (k )

0,5
0,4 n=5 (m = 2k 5)
0,3
0,2
0,1
k
0 1 2 3 4 5

, n , -
, . , ,
n >> 1
( k a )2
1
P(n ) (k ) ~ a = np ; 2 = np(1 p ) ,
2
e 2 ,
2
p 0,5.
p << 1 , ..
,
a
. p= , n1, p1.
n

k nk
a a a k a
Pn (k ) = C 1
k
n ; lim Pn (k ) = e - .
n n n k!
13

( , -
, , ..).

1.3.2.

, t 0 , t1 ,...,
.

t
t0 t1 t2 t3

, 3 :
( , k -
,
;
( ,
k , , -
);
( , -
t 2 -
).
, k ,
:

P (k ) =
( )k e ,
k!

.
k = 0 , ..
P (k ) :

P (0) = e .

+ ,
. , , :

P + (0) = P (0) P (0) .

P (0 ) 1 P (1) .

, ,
:

0 P (0) + 1 P (1),
14

: P (1) .

, : P (0) = 1 ,

.. P + (0) = P (0)(1 ) .

P + (0) P (0)
: = P (0) .

dP (0)
0 : = - P (0) .
d

-
, :
dP (0 )
= - d ;
P (0 )

ln P (0 ) = - + C .

: P0 (0) = 1 ,
.. C = 0 , :
P (0) = e .

k > 0 .
:

m1 { } = ; M 2 { } = .

1.3.3.


P (k ) k ,
( , , -
) .
, , -
.
, , -
.
. -
, P (k ) k = 0 .
.
-
, , :
F ( x ) = P{ x} = 1 P{ > x}.
15
P{ > x} ,
x
:

P{ x} = P (k ) k =0 =
( )k e = e x .
k =0
=x
k! =x

,
F ( x ) = 1 e x .

( -
).
1
= - .

:
x

F ( x ) = 1 e
, x 0.

, :
x
1
W ( x ) = e , x 0.

,

m1 { } =
1


x
( )2
xe
0

dx =

= .

:
x
1 2 2
M 2 { } = m2 { } (m1 { }) = x e dx ( ) = ( ) .
2 2

.
= 100 . , 100
?
:

100

P{ 100} = 1 F (100) = 1 1 e 100 0,37 .

, ,
(-
) k - (k 1) . -
k - , -
:
x

x k 1e x0
W ( x )k = ,
( ) (k 1) !
k
k 1 .
k = 1, , :
x
1
W ( x )1 = W ( x ) = e .

:
16

m1 { } = k
M 2 { } = k ( )
2

1
-. = , -

k . :
x 1 x
W ( x ) , = e , x0 ,
( )

( ) = e t t 1dt - .
0

, :

( ) = e t t 1dt = ( 1) !
0

:

m1 { } = ; M 2 { } = .
2

1.3.4.

, -
(), .
1880 -
. ,
, -

m1 {1 } = m1 { 2 } = 0; M 2 {1 } = M 2 { 2 } = 2 ,
.
= 12 + 22 ,
1 , 2 - -
. , 1 , 2 y, x1 , x 2 :

x2
y

x1
1
17
F ( y ) ,
x1 x2
y = x12 + x22 ,

F ( y ) = W (x , x )dx dx
( ) 2
1 2 1 2 ,
x12 + x22 y


x12 + x22
1
W(2 )
(x1 , x2 ) = e 2 2
.
( 2 )
2

, :
x1 = cos
x 2 = sin

:
( x1 , x2 )
2 y 2
1
F ( y ) = 2 e 2 2
dd ,
0 0
2
( , )

x1 x1
(x1 , x2 ) cos sin
= = =
( , ) x2 x2 sin cos

2 y 2 y2 t y2
2 1
F ( y ) = d = 2
= , y 0.
2 2 2
2 2
, e d e dt 1 e
0 0
2 2
2 0

,
y2
y
W ( y ) = e 2 2
, y 0.
2

W ( y )

2 > 1

y
1 2
18

y = y

y2 y2
1 2 y 2 2 2
e 2 2
e =0,
2 2 4

y =

1
W ( y ) = W ( y )max = .
e


4 2
m1 {} = , M 2 {} = .
2 2

1.3.5.

S (t ) = A(t )cos( 0 t + (t ) + ) ,

A(t ) (t ) - , 0 - -
, .
[0,2 ] . -
. -
:
1
, a xb
W ( x ) = b a
0 x < a, x > b.

W ( x )

1
ba
x
0 a b

m1 { } =
a+b
; M 2 { } =
(b a )2 .
2 12
19
:

0 xa
x a
F ( x ) = a< xb .
b a
1 x>b

F (x )

x
0 a b

1. k = U k U k(l ) , U k -
U (t ), U k(l ) l - . -
k

1
W (x ) = , x .
2

l +1

Uk
l
(l )
Uk

l 1
tk

2
m1 { } = 0 ; M 2 { } = .
12

2. .

1
W ( x ) = , (0 2 )
2
2
1
m1 { } =
2 0
xdx =

M 2 { } = m2 { } m12 { } =
(2 )2 2 = 2
3 3
20

1.4.

1.4.1.

A , n -
() B1 ,..., Bn , . , ,
A ( ) -
y j , n . Bi
yi . P( A, Bi ) , -
yi , y j (
y1 ,..., y n ).
n n
P( A) = P( A, Bi ) = P( A / Bi )P(Bi ) ,
i =1 i =1

P( A, Bi ) A Bi ;
P( A Bi ) A Bi ;
P(Bi ) Bi .
, ,
P( A Bk )P(Bk ) = P(Bk A)P( A),
Bk ()

P( A / Bk )P(Bk ) P( A / Bk )P(Bk )
P ( Bk / A ) = = n
P ( A)
P( A / Bi )P(Bi )
i =1
- .
-
. , :
x + x y

W ( ) ( x, y )dxdy 2

P{x < x + x, y}
P{ y x < x + x} = = . x

P{x < x 1 } x + x

W (x, y )dxdy
( ) 2

W ( x, y ) - .
(2 )

F ( y x ) = lim P{ y x < x + x}.


x 0

:
y y

W (x, y )dyx W (x, y )dy


(2 ) ( ) 2
y
1
F ( y x ) = lim
==
= W ( ) ( x, y )dy .
2
x 0
W ( x )
W (x, y )dyx W (x, y )dy
( ) 2 ( ) 2

F ( y x ) - , -
.
21
F ( y x )
, , ,
y
F ( y x ) W (2 ) ( x, y )
W ( y x ) = =
y W ( x )
W ( y x ) - -
, .
:

1

W ( x )

W ( y x )dy = W (2 ) ( x, y )dy = = 1.
W ( x ) W ( x )
:


W ( y ) = W (2 ) ( x, y )dx = W ( y x )W ( x )dx .

y, F ( y x ) F ( y ) :


y
F ( y ) = W (x ) W ( y x )dy dx = F ( y x )W (x )dx .

W ( y x ) , :
W ( 2 ) ( x, y )
.W ( x y ) =
W ( y )
-
:

W ( y x )W ( x )
W ( x y ) =

W ( y x )W (x )dx

. () .

() (. 1.2.2.), a1 , 12 a 2 , 22 -
.
1
W ( 2 ) ( x, y ) 2 1 r 2 1 2
W ( y x ) = =
W (x ) 1 ( x a1 )2
exp
2 1 2 12
1 ( x a1 )2 (x a1 )( y a2 ) + ( y a2 )2 =
exp 2 r
( 2
2 1 r 1 ) 2
1 2 22
(x a1 )2 2 ( x a1 )
2
( x a1 )( y a 2 ) ( y a 2 )
2
=
1
exp
1
2
( ) 1 r ( )
2r + =
(
2 2 1 r 2 ) 2 1 r 1
2
12 1 2 22

1 1 x a1 y a 2
2

= exp r .
2 2 (1 r 2 ) ( 2
)
2 1 r 1 2

22

, r = 0 , , -
:

( y a2 )2
1
W ( y x ) = e 2 22
= W ( y ).
2 2

, r 1 ( ) :
y a 2 x a1
W ( y x ) .
2 1
, x = a1 r 1
y = a 2 :

W ( y a1 )

r3 > r2

r2 > r1

r1

y
a1 a2

1.4.2.

.
:

yW (x, y )dy
( ) 2

m1 { x} = yW ( y x )dy =

.

W (x )
:

[ y m { x}] W (x, y )dy


( ) 2 2
1

M 2 { x} = [ y m { x}] W ( y x )dy =
2
.
W (x )
1

, :
2
m1 { x} = r ( x a1 ) + a 2
1
(
M 2 { x} = 22 1 r 2 )
23

, r = 0 :

m1 { x} r =0 = a 2 ; M 2 { x} =0 = 22
2
r 1 m1 { x} (x a1 ) + a2 , M 2 { x} 0.
1

1.4.3.

1 ,..., n , n -
W(n ) ( x1 ,..., xn ) . , -
(1.4.1) :
W(n ) (x1 ,..., xn )
W (k )
(x1 ,..., xk xk +1 ,..., xn ) = .
W(n k ) (x k +1 ,..., xn )
, , :

W(n ) ( x1 ,..., x n ) = W ( xn xn 1 ,..., x1 ) W ( xn 1 ,..., x1 ) =


= W (x n xn 1 ,..., x1 ) W ( xn1 x n 2 ,..., x1 ) W ( xn 2 ,..., x1 ) =
= W (x n xn 1 ,..., x1 ) ... W ( x2 x1 ) W ( x1 ) .